Проблеми впровадження системи аналітики поведінки користувачів та сутностей - Пасєка, І.; Сєвєрінов, О. В. (ХНУРЕ, 2019)
Issues of implementation of behavior and object analysis systems (UEBA) are considered. The main tasks and components of UEBA systems are considered. The problems that arise when implementing these systems in the organization are analyzed.
Keywords: аналітика поведінки користувачів; аналітика поведінки сутностей; UBA; UEBA; внутрішній порушник; інсайдер